Age differences on the intention to save in a voluntary retirement fund - Sabri, Mohamad Fazli; Yusof, Radduan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The Theory of Planned Behaviour (TPB) posited that an individual’s intention of performing a behaviour depends on their attitude, subjective norm and the perceived behavioural control (PBC). Employing the theoretical construct of the TPB, this study aims to investigate if age moderatesthe effect of attitude, subjective norms and perceived behavioural control towards saving intention in the voluntary retirement fund in Malaysia. A quantitative approach was adopted with data collected through a nationwide self-administered questionnaire. Through a multistage proportionate stratified sampling, 384 response was collected. The multi-group permutation results confirm the differences between age groups regarding subjective norms towards the intention to save in a voluntary retirement fund in Malaysia. In the concluding remark, the implication of the study and an avenue for future research in voluntary retirement saving domain is discussed.